THE PERFORMANCE OF MICROCONTROLLER-BASED COMPUTER COOLING SYSTEM - Dela Calzada II, Limic M; Go, Marivel B; Vallente, Dante T; Culpable, Rex V; Ator, Jefrey I; Pableo, Romeo G (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 1, 2015, 2015)
Overheating of the computer would damage the integral parts of what makes the computer work. Thus, monitoring the temperature inside the System Unit of a computer is critical task to ensure the performance is not disturbed by excessive room temperature. In the Philippines, it is necessary to incorporate a separate cooling system to maintain computers from getting damaged by heat since these computers were designed in other countries with much lower room temperatures. Hence, this study was conducted to fabricate a prototype design of a microcontroller-based computer cooling system with smart characteristics to cool components inside the System Unit and prevent damage the hardware parts. The device uses AT89C2051 microcontroller and DS18B20 Thermal Sensor. It is also equipped with a seven-segment display to provide monitoring of the System Unit’s temperature. The device took temperature reading from the temperature sensors and displayed real time temperatures. It decided to turn on the fan and control its speed of rotation depending on the temperature of the heated components or to keep it off if its temperature is lower than the trigger temperature. It rotates on the following percentages: 25%, 50%, 75% and 100%. Statistically, the computer with the Microcontroller-based Computer Cooling System has significantly (p<0.05) reduced the temperature of the components inside the System unit. It is therefore recommended for use in school computers to prevent from damage and shortening the lifespan of the hardware.